Risk Management, Green Finance, CSR, and Digital Transformation Effects on Financial Sustainability in KBMI Banks - Michael Jims; Pardomuan Sihombing (Journal of Sustainable Economic and Business, 2026)
Objectives: This study investigates whether risk management, green finance, corporate social responsibility, and digital transformation explain financial sustainability among Indonesian commercial banks in core-capital bank groups 3–4 (KBMI 3–4). Methodology: Using a balanced panel of 13 listed banks over 2022–2024 (39 bank-year observations), we estimate a panel regression under a random-effects specification selected via Chow, Hausman, and Lagrange Multiplier tests. Financial sustainability is proxied by the net interest margin ratio, while the explanatory variables are proxied by the non-performing loan ratio, green investment ratio, corporate social responsibility expenditure ratio, and a digital transformation index. Finding: The findings demonstrate that green finance significantly enhances financial sustainability among KBMI 3 and 4 banks during 2022-2024. Meanwhile, risk management, corporate social responsibility, and digital transformation do not exhibit significant short-term effects on net interest margins. Therefore, banks should prioritize credible green financing portfolios while maintaining strict credit quality, and investors must evaluate sustainability signals beyond short-term margin impacts. Conclusion: Research on SMEs in Indonesia increasingly emphasizes external shocks and digital transformation strategies. The evidence suggests that digital technology adoption combined with innovation, supported by training and enabling policies is essential to strengthen SMEs’ competitiveness and long-term sustainability in Indonesia.